Aplikasi Smart Title Checker Laporan Mahasiswa Menggunakan Metode Cosine Similarity Berbasis Website Pada Politeknik Xyz - Yudistira Sira Permana; Muhammad Syahril; Agus Setiawan (Riau Jurnal Teknik Informatika, 2026)
The increasing number of student final reports each year presents challenges for higher education institutions in maintaining the uniqueness and novelty of proposed titles. The title-checking process, which is still commonly conducted manually, tends to require considerable time and may lead to inconsistencies in the validation process. This study aims to design and develop a web-based Smart Title Checker application capable of detecting the similarity level of student report titles using the Cosine Similarity method. This method is applied to measure the similarity between titles, thereby supporting a more objective validation process. The system development was carried out through several stages, including requirements analysis, design, implementation, and application testing. The results show that the application can perform title similarity checking quickly and accurately by displaying similarity percentages against stored title data in the database. The system implementation also helps students obtain initial information regarding potential title similarities and improves the efficiency of the validation process conducted by academic administrators. Therefore, the developed application can support more effective, efficient, and structured management of student report titles.